Effect of interface morphology on the residual stress distribution in solid oxide fuel cell. (3rd February 2020) - Li, Qiangqiang; Li, Guojun; Cao, Ganglin; Zhang, Xiongwen; Cheng, Mincan; Ma, Yanfei
Summary: Solid oxide fuel cell directly and efficiently converts chemical energy to electrical energy. However, the necessity for high operating temperatures can result in mechanical failure. Fuel cell is a multilayer system and its stress distribution is greatly affected by the interface morphology. In this work, cosine interfaces with different amplitudes are used to approximate the fluctuation of actual interface. The effects of interface morphology on stress state, energy release rate of crack and creep behavior have been investigated. The results show that if the interface is planar, the residual normal stress component is zero on the interface, while the nonplanarity of interface can cause the normal stress S n and shear stress S t on the interface. When the amplitude is relatively small, the max values of S n and S t on the interfaces vary linearly with increasing amplitudes in both anode and cathode. Above a certain value, nonlinearity of the interface becomes important. Max tensile S n always occurs at the peak of convex interface, but the position of max compressive S n varies. Max shear stress is prone to occur at 1/4 of the wavelength at small amplitude and moves towards 1/2 of the wavelength when the amplitude increases. Fracture mechanics analysis shows that the surface crack possibly penetrates into the anode function layer and then is constrained by the stiff electrolyte. On the other hand, the horizontal crack likely penetrates into the electrolyte layer when the interface is not planar. Creep analysis shows that 11 800 hours of continuous operation at high temperature cannot remove stress undulation introduced by nor‐planar interface but can make max value of Sn and St decrease around 30%. Abstract : If the interface is planar, the residual normal stress Sn is zero on the interface, while the non‐planarity of interface can cause the normal stress Sn on the interface. Max tensile Sn always occurs at the peak of convex interface, but the position of max compressive Sn varies. When the amplitude is relatively small, the max values of Sn on the interfaces vary linearly with increasing amplitudes.